Automated Fractional Limb Volume Measurements Improve the Precision of Birth Weight Predictions in Late Third‐Trimester Fetuses. (25th April 2017) - Mack, Lauren M.; Kim, Sung Yoon; Lee, Sungmin; Sangi‐Haghpeykar, Haleh; Lee, Wesley
Abstract : Objectives: Fetal soft tissue can be assessed by using fractional limb volume as a proxy for in utero nutritional status. We investigated automated fractional limb volume for rapid estimate fetal weight assessment. Methods: Pregnant women were prospectively scanned for 2‐ and 3‐dimensional fetal biometric measurements within 4 days of delivery. Performance of birth weight prediction models was compared: (1) Hadlock ( Am J Obstet Gynecol 1985; 151:333–337; biparietal diameter, abdominal circumference, and femur diaphysis length); and (2) Lee ( Ultrasound Obstet Gynecol 2009; 34:556–565; biparietal diameter, abdominal circumference, and automated fractional limb volume). Percent differences were calculated: [(estimated birth weight – actual birth weight) ÷ (actual birth weight] × 100. Systematic errors (accuracy) were summarized as signed mean percent differences. Random errors (precision) were calculated as ± 1 SD of percent differences. Results: Fifty neonates were delivered at 39.4 weeks' gestation. The Hadlock model generated the most accurate birth weight (0.31%) with a mean random error of ±7.9%. Despite systematic underestimations, the most precise results occurred with fractional arm volume (−9.1% ± 5.1%) and fractional thigh (−5.2% ± 5.2%) models. The size and distribution of these prediction errors were improved after correction for systematic errors. Conclusions: Automated fractional limb volume measurements can improve the precision of weight predictions in third‐trimester fetuses. Correction factors may be necessary to adjust underestimated systematic errors when using automated fractional limb volume with prediction models that are based on manual tracing of fetal limb soft tissue borders.